2013
DOI: 10.1111/anu.12013
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an upper level of intake for vitamin A in Atlantic salmon (Salmo salarL.) postsmolts

Abstract: The vitamin A (VA) concentration in salmon aquaculture feeds is varying and may lead to sublethal adverse effects. In this study, 135 g Atlantic salmon postsmolts were given eight diets in duplicates with 6, 12, 26, 55, 82, 112, 360 and 749 mg retinol (ROL) kg À1 for 116 days. Subsequently, fish given 6, 82 and 749 mg ROL kg À1 were transferred to a common net pen and given a standard commercial diet for further 28 weeks. Feed conversion rate, liver functionality and markers of VA homoeostasis were not negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…A number of factors are known to increase the risk of jaw deformities in production fish including suboptimal temperatures (Bolla & Holmefjord 1988), nutritional deficiencies (Vitamin A, Ørnsrud et al 2013), and light source and tank colour (Bolla & Holmefjord 1988;Cobcroft & Battaglene 2009). In the current study, it is unknown whether the observed jaw deformities were caused by physiological differences or mechanical damage through differences in behaviour (Morrison & Macdonald 1995) or ventilation rates (Roberts, Hardy & Sugiura 2001;Ørnsrud et al 2013). It is possible that triploids were suffering from phosphorus deficiency (see above), but it is also interesting to note that triploid salmon are suggested to have lower temperature optima than diploids with higher metabolic rates at similar temperatures to those used in the current study (i.e.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A number of factors are known to increase the risk of jaw deformities in production fish including suboptimal temperatures (Bolla & Holmefjord 1988), nutritional deficiencies (Vitamin A, Ørnsrud et al 2013), and light source and tank colour (Bolla & Holmefjord 1988;Cobcroft & Battaglene 2009). In the current study, it is unknown whether the observed jaw deformities were caused by physiological differences or mechanical damage through differences in behaviour (Morrison & Macdonald 1995) or ventilation rates (Roberts, Hardy & Sugiura 2001;Ørnsrud et al 2013). It is possible that triploids were suffering from phosphorus deficiency (see above), but it is also interesting to note that triploid salmon are suggested to have lower temperature optima than diploids with higher metabolic rates at similar temperatures to those used in the current study (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…In the current study, it is unknown whether the observed jaw deformities were caused by physiological differences or mechanical damage through differences in behaviour (Morrison & Macdonald ) or ventilation rates (Roberts, Hardy & Sugiura ; Ørnsrud et al . ). It is possible that triploids were suffering from phosphorus deficiency (see above), but it is also interesting to note that triploid salmon are suggested to have lower temperature optima than diploids with higher metabolic rates at similar temperatures to those used in the current study (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hypervitaminosis has been reported for fat-soluble vitamins such as vitamins A and D (Hilton 1983). High dietary intakes of vitamin A may cause toxic effects in certain fish (Atlantic salmon, Japanese flounder, Paralichthys olivaceus, tilapia, Oreochromis niloticus) and the main toxic effects are associated with bone malformation (Dedi et al 1995(Dedi et al , 1997Ørnsrud et al 2002, 2013Saleh et al 1995). The sensitivity to hypervitaminosis A appears to be species specific and life stage dependent in fish, which has also been shown for mammals (Nau et al 1994).…”
Section: Biotin Toxicitymentioning
confidence: 94%
“…The sensitivity to hypervitaminosis A appears to be species specific and life stage dependent in fish, which has also been shown for mammals (Nau et al 1994). This difference in toxicity between water-and fat-soluble vitamins is due to the fact that excess water-soluble vitamin is excreted by the fish, while excess fat-soluble vitamin is accumulated in the lipid fraction of the fish body (Olivia-Teles 2012; Ørnsrud et al 2002, 2013Halver 2002). Since biotin is not retained in the body, the maximum tolerable limit or toxicity of this vitamin may not be a concern for fish and other animals (NRC 1987).…”
Section: Biotin Toxicitymentioning
confidence: 99%